Smart Campus Evaluation Monitoring Model Using Rainbow Framework Evaluation and Higher Education Quality Assurance Approach - Irfan Santiko; Anugerah Bagus Wijaya; Aulia Hamdi (Universitas Bina Darma, 2022)
Education in the industrial era 4.0 experienced very significant changes. The role of information technology is a significant trend in education. Since the pandemic occurred at the beginning of 2020, almost all schools and even universities have indirectly demanded rapid changes in adapting to digitalization methods. It was also found that there were many obstacles during the pandemic in the implementation of information technology. The Indonesian state itself in education is still adapting and starting to develop with the existence of models of information technology approaches that can be implemented in academic activities, especially on campuses. Since 2010 it has been following the smart campus concept and model development. However, it was found to be varied due to the absence of a benchmark index in the campus's preparation, monitoring, and evaluation. Through the Rainbow Framework, this will be a solution in measuring the feasibility level through monitoring and evaluating the use of technology with a quality assurance approach. The results can be seen from the components that have been built using the calculation model for the quality of technology education in Indonesia.